We have plenty of words written down; we need melodies! - Kunej, Drago (Traditiones (Ljubljana), 2005)
This paper examines the endeavors of the Committe for the Collection of Slovenian Folk Song (OSNP) to acquire its first recording device for field sound recordings. The committee's large-scale plans to purchase two phonographs and a great number of wax cylinder were highly advanced for the time because this would enable systematic folk song research based on sound recording with archived cylinders serving as references for notation and as a primary source. Unfprtunately, the plans had to be curtailed considerably and were only carried out towards the end of the collection campaign
Keywords: Štrekelj, Karel, 1859-1912; fonografi; zvočna snemanja; zvočni arhivi; slovenske ljudske pesmi; zgodovinski pregledi